A third-order range separation imaging algorithm for manoeuvring platform SAR. Issue 8 (3rd August 2019) - Hou, Jianqiang; Ma, Yanheng; Li, Gen
ABSTRACT: Occurrence of various travel trajectories poses a challenge in synthetic aperture radar (SAR) imaging. A method is proposed to solve this problem. After distance compression, the range equation is decomposed into terms that are not related to the position of the target points, and items that are not related to the azimuth parameters, to solve the problem of range migration correction and spatial-variant component correction. Then, the three-dimensional uniformly accelerated motion model is equivalent to the traditional uniformly accelerated linear model. Based on the equivalent model, azimuth bending correction and azimuth compression can be realized simply and quickly. The simulation results show that the proposed algorithm has good imaging effect. It can also get that the algorithm has wider applicability and can be used for SAR imaging in different motion models.